'Smart cities' and citizenship. (5th April 2022) - Kumar, Deepak
The Smart Cities Mission in India was launched on 25 June 2015 to develop 100 'smart cities'. Harnessing technology to improve the quality of life of people in such cities is the core idea of the mission. This urban governance mechanism has inherent implications for citizenship as a membership right assuming those having membership of such cities enjoying a host of citizenship rights for example access to basic services at the cost of those excluded. In this context, the paper attempts to explore the Smart Cities Mission in India, emerging scholarship on smart cities and citizenship, and the notion of citizenship as membership rights for delineating the implication of the mission on citizenship rights of the deprived sections.